UPAYA UNIT DIKYASA MELALUI PROGRAM RADIO TALK SHOW DALAM MENGURANGI PELANGGARAN LALU LINTAS KARYAWAN SWASTA - indra kurniawan (Advances in Police Science Research Journal, 2020)
traffic violations committed by private employees is highest in the Cianjur Regional Police Station. Preventive actions taken with the talk show radio program, but the interest of radio listeners decreases, so it takes the efforts of Dikyasa Unit so that messages through the radio can be conveyed to private employees. Therefore, a study was conducted which aimed to find out traffic violations by private employees, efforts of the Dikyasa Unit through a radio talk show program, influential factors. Theories and concepts used are law enforcement theory, management theory, FFA theory, effort concept, community education concept, broadcast concept, radio talk show concept, traffic violation concept, and private employee concept. This research was conducted with a qualitative approach, using descriptive analysis research methods, as well as data collection techniques by interviewing, observing, and studying documents. The results found that the understanding of private employees about the importance of orderly traffic is very low, the short distance is the main reason private employees do not use helmets. Members never prepare material to be delivered. With the broadcasting system through radio broadcasts it becomes a supporting factor, so that private employees can receive messages that are conveyed as a whole. Factors that hinder radio talk show programs are the busyness of private employees who cannot listen to the radio. Based on the results of the study, the authors suggest to prepare the material presented in order to be interesting, coordinate with the radio station and other agencies in socializing radio talk show programs, coordinate with all companies in Cianjur Resort Police to provide radio facilities that can be heard by all private employees while working or resting at all companies in the Cianjur Regional Police Station.